Unlocking Consumer Behavior: The Impact of DANA E-Wallet, Lifestyle, and Self-Control - Riski Saputri; Agus Setiawan (Presscience, 2024)
The purpose of this study is to examine how the use of DANA e-wallet, lifestyle, and self-control influence consumer behavior. A closed-ended questionnaire distributed online via social media was used to collect data for this research. Employing non-probability sampling techniques with purposive sampling method, a sample of 120 respondents was selected. The collected data were analyzed using multiple linear regression analysis. The results of this study indicate that the use of DANA e-wallet has a positive but not significant partial effect, lifestyle has a positive and significant partial effect, and self-control has a positive but not significant partial effect. Additionally, collectively, the use of DANA e-wallet, lifestyle, and self-control significantly influence consumer behavior.